Paradoxical interaction between cancer and long-term postsepsis disorder: impairment of de novo carcinogenesis versus favoring the growth of established tumors. Issue 1 (5th May 2020) - Leite, Caio Abner; Mota, Jose Mauricio; de Lima, Kalil Alves; Wanderley, Carlos Wagner; Nascimento, Leticia Almeida; Ferreira, Marcela Davoli; Silva, Camila Meirelles Souza; Colon, David Fernando; Sakita, Juliana Yumi; Kannen, Vinicius; Viacava, Paula Ramos; Begnami, Maria Dirlei; et al.
Abstract : Background: Previous data have reported that the growth of established tumors may be facilitated by postsepsis disorder through changes in the microenvironment and immune dysfunction. However, the influence of postsepsis disorder in initial carcinogenesis remains elusive. Methods: In the present work, the effect of postsepsis on inflammation-induced early carcinogenesis was evaluated in an experimental model of colitis-associated colorectal cancer (CAC). We also analyzed the frequency and role of intestinal T regulatory cells (Treg) in CAC carcinogenesis. Results: The colitis grade and the tumor development rate were evaluated postmortem or in vivo through serial colonoscopies. Sepsis-surviving mice (SSM) presented with a lower colonic DNA damage, polyp incidence, reduced tumor load, and milder colitis than their sham-operated counterparts. Ablating Treg led to restoration of the ability to develop colitis and tumor polyps in the SSM, in a similar fashion to that in the sham-operated mice. On the other hand, the growth of subcutaneously inoculated MC38luc colorectal cancer cells or previously established chemical CAC tumors was increased in SSM. Conclusion: Our results provide evidence that postsepsis disorder has a dual effect in cancer development, inhibiting inflammation-induced early carcinogenesis in a Treg-dependent manner, while increasing the growth of previously established tumors.